6(7−3y)+6(y+1) please help
2 answers:
Answer: 4=y
Step-by-step explanation:
6(7 -3y)+6(y+1)
42-18y+6y+6
48-12y
48/12=4
12y/12=y
4=y
Answer:
-12y+48
Step-by-step explanation:
6(7−3y)+6(y+1)
Distribute:
=(6)(7)+(6)(−3y)+(6)(y)+(6)(1)
=42+−18y+6y+6
Combine Like Terms:
=42+−18y+6y+6
=(−18y+6y)+(42+6)
You might be interested in
Answer:
32 centemeters
Step-by-step explanation:
Answer:
420 in³
Step-by-step explanation:
14 x 10 x 3 = 420
Answer:
1/2
Step-by-step explanation:
Answer:
A(0,-3) B (5,0) C(0,-7)D(5,-4)
Step-by-step explanation:
Answer: 19.615
Step-by-step explanation:
510 ÷ 26 = 19.615